Look at Me: I Love My Family - Octopus Publishing Group (Octopus Publishing Group, 2001)
Babies love looking at babies, and these two books are packed full of photographs for even the youngest baby to enjoy. The small format is perfect for little hands to hold, and turning the pages will help to develop hand-eye coordination.
Keywords: Family; General; Juvenile Fiction